2020
DOI: 10.1038/s41598-020-57755-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical forces induce an asthma gene signature in healthy airway epithelial cells

Abstract: Bronchospasm compresses the bronchial epithelium, and this compressive stress has been implicated in asthma pathogenesis. However, the molecular mechanisms by which this compressive stress alters pathways relevant to disease are not well understood. Using air-liquid interface cultures of primary human bronchial epithelial cells derived from non-asthmatic donors and asthmatic donors, we applied a compressive stress and then used a network approach to map resulting changes in the molecular interactome. In cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 94 publications
(86 reference statements)
1
31
1
Order By: Relevance
“…HBECs, grew them to confluence under Air Liquid Interface (ALI), and then exposed them to an apico-to-basal pressure difference of 30 cm H2O 15,26,29,30,[36][37][38] (see Materials and Methods). Following the same experimental protocol described in Kılıç et al 30 , this pressure was maintained for 3 hours and then released ( Fig. 1a).…”
Section: Compression-induced Ujt Activates a Bimodal Transcriptional mentioning
confidence: 99%
See 2 more Smart Citations
“…HBECs, grew them to confluence under Air Liquid Interface (ALI), and then exposed them to an apico-to-basal pressure difference of 30 cm H2O 15,26,29,30,[36][37][38] (see Materials and Methods). Following the same experimental protocol described in Kılıç et al 30 , this pressure was maintained for 3 hours and then released ( Fig. 1a).…”
Section: Compression-induced Ujt Activates a Bimodal Transcriptional mentioning
confidence: 99%
“…Compared with HBECs derived from non-asthmatic donors, HBECs derived from asthmatic donors exhibit phenotypic characteristics of unjammed tissues, with more elongated shapes and prominent collective migratory behavior 11 . At the transcriptional level, a recent study has shown that asthmatic HBECs and nonasthmatic HBECs at 24 hours post-compression exhibit similar transcriptional patterns as genes associated with airway remodeling and ECM reorganization 30 .…”
Section: Flow Centrality Identifies Ecm Remodeling Proteins As Key Rementioning
confidence: 99%
See 1 more Smart Citation
“…UJT is known to occur during embryonic development 19 , 20 , injury repair 21 , tumor metastasis 22 , 23 , and in the asthmatic airways 19 , 24 . Both the UJT and the EMT potentiate epithelial plasticity and migration, but underlying mechanisms of UJT versus EMT are distinct 19 , 20 , 25 , 26 . Unlike the case of the EMT, for example, in the case of the UJT the cell–cell junction and barrier function remain fully intact 25 .…”
Section: Introductionmentioning
confidence: 99%
“…UJT is known to occur during embryonic development 19,20 , injury repair 21 , tumor metastasis 22,23 , and in the asthmatic airways 19,24 . Both the UJT and the EMT potentiate epithelial plasticity and migration, but underlying mechanisms of UJT versus EMT are distinct 19,20,25,26 . Unlike the case of the EMT, for example, in the case of the UJT the cell-cell junction and barrier function remain fully intact 25 .…”
Section: Introductionmentioning
confidence: 99%